PLURALISME AGAMA MENURUT NURCHOLIS MADJID (1939-2005) DALAM KONTEKS KEINDONESIAAN - Catur Widiat Moko (Medina-te : Jurnal Studi Islam, 2017)
This research entitled "Religious Pluralism According to Nurcholish Madjid in Indonesian Context '. Based on the phenomenon that occurred in the field many Muslims who more emphasize the symbol of religion than the application in menjlankan religion so that underlie thinking Nurcholis Madjid in overcoming msalah.dilakukan three stages of work that is Inventory, Evaluation, and Synthesis. The writings that have been obtained will be reviewed, an analysis of the thoughts of Nurcholish Madjid. The research approach is historical approach, while in historical research using heuristic technique, verification, intervention, and historicistography. The results of this study can be summarized as follows, First, the basis of religious pluralism is that the universal religion of Islam encompasses all aspects of life, Pancasila is the foundation of the state of Indonesia so that we must do tolerance and compete in the good. Secondly, that the implications of religious pluralism recognize religious freedom, live with the risks that will be borne by each believer. The will of God is above the will of man in setting anything. Thirdly, the principle of religious pluralism is the open, dialogical, tolerant and upholding of human values which at the same time embodies a peaceful and open Islam.